2005
DOI: 10.1097/01.shk.0000170354.18437.2f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bovine Polymerized Hemoglobin on Coagulation in Controlled Hemorrhagic Shock in Swine

Abstract: HBOC-201, a bovine polymerized hemoglobin, has been proposed as a novel oxygen-carrying resuscitative fluid for patients with hemorrhagic shock (HS). Herein, we evaluated the hemostatic effects of HBOC-201 in an animal model of HS. A 40% blood loss-controlled hemorrhage and soft tissue injury were performed in 24 invasively monitored Yucatan mini-pigs. Pigs were resuscitated with HBOC-201 (HBOC) or hydroxyethyl starch (HEX), or were not resuscitated (NON) based on cardiac parameters during a 4-h prehospital ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
6
22
0
Order By: Relevance
“…Although a number of preclinical studies of HBOC-201 have been performed and its efficacy has been demonstrated [32], to best of our knowledge, pharmacokinetic studies of HBOC-201 in preclinical trials are limited, due to the fact that the half-life of HBOC-201 is around 22 h in a 40% hemorrhagic shock model of a Yucatan mini-pig [33] (or have not been published). On the other hand, the safety and efficacy of HBOC-201 has been examined in more than 20 clinical trials [34], some in which the half-life of HBOC-201 in humans were reported (Table 2).…”
Section: Acellular Type Hbocsmentioning
confidence: 99%
“…Although a number of preclinical studies of HBOC-201 have been performed and its efficacy has been demonstrated [32], to best of our knowledge, pharmacokinetic studies of HBOC-201 in preclinical trials are limited, due to the fact that the half-life of HBOC-201 is around 22 h in a 40% hemorrhagic shock model of a Yucatan mini-pig [33] (or have not been published). On the other hand, the safety and efficacy of HBOC-201 has been examined in more than 20 clinical trials [34], some in which the half-life of HBOC-201 in humans were reported (Table 2).…”
Section: Acellular Type Hbocsmentioning
confidence: 99%
“…Although several potential mechanisms may explain the vasoconstrictive properties of these HBOCs (10, 13, 14), nitric oxide (NO) scavenging by the HBOCs is the most likely (1, 4, 15–17). Recently, this laboratory has confirmed that glutaraldehyde-polymerized bovine HBOC infusion in animals had dire consequences on hemodynamic performance in both normoxic and hypoxic rats (18).…”
mentioning
confidence: 99%
“…These findings suggest that using HbV initially might be advantageous in patients having massive hemorrhages, although they cast doubt on the coagulation influence that has been suggested previously (21). Encapsulated Hb, which is one of the next generation of HBOCs, includes some RBC enzymes (22) and is permeable to glucose and other small hydrophilic molecules.…”
Section: Discussionmentioning
confidence: 82%